The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1598/rrq.43.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Biliteracy in Young Mexican Immigrant Children

Abstract: This article explores the relationship between emergent biliteracy and growing up in a biliterate environment. The study focuses on two questions: (1) What knowledge of biliteracy do young bilingual preschool children develop in the early years? (2) How do context and specific language environments influence the development of biliteracy in young Mexican Spanish‐English bilingual children? The authors report data from a multiple‐method research project with 12 4‐ and 5‐year‐old Mexican immigrant children livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Among the limited intervention research on storybook reading with ELs, findings have shown contributions of the frequency of home reading (Collins, 2010) and the utility of reading in the L1 or L2 to L2 vocabulary learning (Roberts, 2008). Descriptive studies have shown that storybook reading is common, that storybook reading takes place in primary and second languages (Reyes & Azuara, 2008), and that discussion aids comprehension (Iddings, Risko, & Rampulla, 2009). Less is known about the amounts of talk and interaction that are optimal for learning (Hammett, van Kleeck, & Huberty, 2003), how the demand of talk (Danis et al, 2000) affects comprehension, and how child and family variables interact in monolinguals or ELs.…”
Section: Problems In Current Researchmentioning
confidence: 99%
“…Among the limited intervention research on storybook reading with ELs, findings have shown contributions of the frequency of home reading (Collins, 2010) and the utility of reading in the L1 or L2 to L2 vocabulary learning (Roberts, 2008). Descriptive studies have shown that storybook reading is common, that storybook reading takes place in primary and second languages (Reyes & Azuara, 2008), and that discussion aids comprehension (Iddings, Risko, & Rampulla, 2009). Less is known about the amounts of talk and interaction that are optimal for learning (Hammett, van Kleeck, & Huberty, 2003), how the demand of talk (Danis et al, 2000) affects comprehension, and how child and family variables interact in monolinguals or ELs.…”
Section: Problems In Current Researchmentioning
confidence: 99%
“…This environmental print can facilitate early writing and reading by providing early success and exemplars for copying (Reyes & Azuara, 2008). Recognising this, teachers seek out or create signs that provide language input for their students.…”
Section: Sign-making Practices In Schoolsmentioning
confidence: 99%
“…biliteracy), Reyes and Azuara (2008) examine the relationship between this emerging biliteracy and one's environment, as bilingual children negotiate two languages in the different contexts of home, school and neighbourhood. In some cases, children see signage in their home language in their neighbourhood, but not at school (Moore, 2010), but where the bilingualism is a goal of the classroom, teachers purposefully provide environmental print in both languages (Brown, 2012).…”
Section: Sign-making Practices In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, I review studies that take a sociocultural approach in describing how families and communities affect biliteracy by emphasizing different aspects or factors that impact the process. Although the studies vary in terms of methodology, many of them involve single case studies with natural observations and descriptions of an individual child's biliteracy development (e.g., Bauer & Mkhize, 2012;Buckwalter & Lo, 2002) or observations of a smaller set of children who were part of a larger research project (Drury, 2004;Gregory et al, 2004;I. Reyes & Azuara, 2008;Yaden & Tsai, 2012).…”
Section: Biliteracy In Community and Family Contextsmentioning
confidence: 99%